Islamism and Jahiliyyah: On chaotic terminology and violence structures - Faraj, Rita (Münster journal for Islamic and philosophical studies, 2023)
With the increasing literature researching Islamist movements‭, ‬there has been a great confusion of nomenclature‭. ‬Terms such as Islamic movements‭, ‬fundamentalism‭, ‬political Islam‭, ‬Salafism‭ (‬Dawah‭: ‬scientific and Jihadism‭) ‬and Sahwa‭ (‬Awakening‭) ‬movement‭, ‬are‭ ‬tossed around and lumped together all too often‭. ‬This essay aims‭, ‬firstly‭, ‬to address this confusion and try to untangle it‭. ‬Secondly‭, ‬the paper also presents the textual structures and layers of violence according to the interpretations of Islamist movements‭, ‬through approaching‭ ‬“Jahiliyyah”‭, ‬a term that is mostly used in the literature of Sayyid Qutb‭, ‬whose ideas‭, ‬tremendously‭, ‬influenced contemporary Islamist movement‭.‬